Model Kepemimpinan Modern di Program Pascasarjana Universitas Ahmad Dahlan - Dwi Sulisworo (Journal of Education and Learning (EduLearn), 2012)
In the management of higher education, demand a change can be done effectively when the leadership and management are well developed. In general, internal conflicts in the education management occurred due to poor leadership. This study is a qualitative study with a phenomenological approach. The subject of the study is Graduate Program of University Ahmad Dahlan which manages five master programs. Determination of each of people which considers his/her competence, knowledge, experience and personal attributes will affect to performance and operational leadership roles, organizational, and public. Cross-departmental activities and external parties become a focus for leadership in achieving the vision and mission of the organization.